Influence Of Work Environment And Social Support On Nurse Performance At Tzu Chi Hospital With Organizational Culture As An Intervening Variable - Rina Wahyuni; Arrozi Adhikara; Kemala Rita (Lembaga Pengembangan Kinerja Dosen, 2024)
Human resources have an important position for an organization or company. Human resources play a dominant role in carrying out company operations and achieving predetermined goals. Therefore, organizations need to respect all aspects of employees in order to create quality human resources and superior performance. Superior performance can be achieved through a quality work environment, social support and organizational culture. The aim of this research is to analyze the simultaneous influence of the work environment and social support on the performance of nurses at Tzu Chi Hospital with work organizational culture as an intervening variable. The research method used is data analys. The population of this study was 142 nurses (full time) who had worked for more than 1 year at Tzu Chi Hospital. The sample in this study was all nurses (full time) who had worked for more than 1 year at Tzu Chi Hospital totaling 142 people. Research results: There is a significant influence between the work environment on organizational culture with an influence of 0.373 or 37.3%, there is a significant influence of social support on organizational culture with a large influence of 0.511 or 51.1%, there is a significant influence of the work environment on employee performance with an influence of 0.475 or 47.5%, there is no significant influence of social support and organizational culture on employee performance.